The Evolution of Natural Gas Prices in EU Countries and their Impact on the Country?s Macroeconomic Indicators - Liptáková, Erika; Rimár, Miroslav; Kizek, Ján; Šefčiková, Zuzana (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article, the authors characterize the current European market with natural gas, describing differences in prices for households and prices for companies from the point of view of individual components, where they focus more on taxes, levies and fees. The article further deals with the possible impact of the price of natural gas on the country`s economy, more specifically, the correlation with inflation, unemployment and interest rates.
Keywords: natural gas; gas prices components; correlation; econometric model; Harmonised Index of Consumer Prices (HICP); gaz ziemny; cena gazu; korelacja; model ekonometryczny